2011
DOI: 10.1111/j.1399-3038.2011.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

The EuroPrevall birth cohort study on food allergy: baseline characteristics of 12,000 newborns and their families from nine European countries

Abstract: It is unclear why some children develop food allergy. The EuroPrevall birth cohort was established to examine regional differences in the prevalence and risk factors of food allergy in European children using gold-standard diagnostic criteria. The aim of this report was to describe pre-, post-natal and environmental characteristics among the participating countries. In nine countries across four major European climatic regions, mothers and their newborns were enrolled from October 2005 through February 2010. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 29 publications
0
105
0
8
Order By: Relevance
“…Because of high cost of diagnostic methods of FA, the most reasonable method in prevelance studies is to determine potential children with questionnaire forms and by testing these children. In many studies, 30-fold differences between family reports and actual prevelances of FA have been observed (4,8,23). Therefore, children with a suspicion of FA should be reevaluated with laboratory methods including SPT and DBPCCT to determine the prevelance of FA more accurately in our region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of high cost of diagnostic methods of FA, the most reasonable method in prevelance studies is to determine potential children with questionnaire forms and by testing these children. In many studies, 30-fold differences between family reports and actual prevelances of FA have been observed (4,8,23). Therefore, children with a suspicion of FA should be reevaluated with laboratory methods including SPT and DBPCCT to determine the prevelance of FA more accurately in our region.…”
Section: Discussionmentioning
confidence: 99%
“…This increase has been related with causes including change in diet contents (high rates of antioxidants, fats and high-energy foods), preperation methods of foods (fried, baked or boiled nut), delayed oral contact, maternal and infant diet, contact by topical ways and use of antacids (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PIFA (Prevalence of Infant Food Allergy) study is a prospective birth cohort of 1140 infants recruited between 2006 and 2008, and it was the UK cohort of the EuroPrevall project 14 with study size and eligibility criteria determined by that study' s protocol. 15 15 ) and their 2 age-matched controls were included in a "nested within a cohort, case-control study."…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted in Europe have shown that allergic hypersensitivity to food is a significant clinical problem with increasing prevalence [1].…”
Section: Introductionmentioning
confidence: 99%